2015
DOI: 10.1111/risa.12482
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Population, Contact, and Spatial Heterogeneity on Epidemic Model Predictions

Abstract: Our objective was to evaluate the effect that complexity in the form of different levels of spatial, population, and contact heterogeneity has in the predictions of a mechanistic epidemic model. A model that simulates the spatiotemporal spread of infectious diseases between animal populations was developed. Sixteen scenarios of foot-and-mouth disease infection in cattle were analyzed, involving combinations of the following factors: multiple production-types (PT) with heterogeneous contact and population struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…The use of simple models to produce interesting results has been advocated by Zagmutt et al. (, p.951). However, in the context of risk within a spatial setting, mechanisms for transmission may be nontrivial.…”
Section: A Framework For Spatial Transmission Modeling Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of simple models to produce interesting results has been advocated by Zagmutt et al. (, p.951). However, in the context of risk within a spatial setting, mechanisms for transmission may be nontrivial.…”
Section: A Framework For Spatial Transmission Modeling Approachesmentioning
confidence: 99%
“…; Riley, ), but also in fields as diverse as connectivity on wireless networks (Andrews, Ganti, Haenggi, Jindal, & Weber, ), the spread of fire (Rothermel, ), marketing (Bradlow et al., ), and the diffusion of technology (Berger, ). Risk analysis models that model the transmission of threats around a system include analytical models for epidemiological studies (Eisenberg, Seto, Olivieri, & Spear, ; Moreno & Alvar, ; Zagmutt, Schoenbaum, & Hill, ), cellular automata models for nuclear terrorism (Atkinson, Cao, & Wein, ), soil contamination (Cox, ) and species invasion (Sikder, Mal‐Sarkar, & Mal, ), domain‐based studies of exposure to ozone (Fann et al., ), network models for communication (Dettmann & Georgiou, ), power networks (Zio & Sansavini, ), and in the social amplification of risk (Kasperson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3) The importance of wealth exposure evaluation in disaster risk assessment is widely recognized, (4)(5)(6)(7)(8) and spatial variability (or heterogeneity) is increasingly recognized as a key component in environmental exposure and risk assessment, (9)(10)(11) but high spatial resolution data on actually exposed assets are lacking or not sufficiently detailed. (12) Bouwer et al (13) projected both future land use change and future increase of asset value combined with flood scenarios to estimate the flood risk in the Netherlands, and indicated that asset value increase plays a large role in flood losses increase.…”
Section: Introductionmentioning
confidence: 99%
“…Malczewski reviews many instances of relevant spatial decision problems. These preference models can also be used to support spatial risk analyses, for instance, in the context of epidemics presented by Zagmutt et al ., or incorporating vulnerability to natural disasters, as explored by Zhou et al …”
Section: Introductionmentioning
confidence: 99%
“…(2) Malczewski (3) reviews many instances of relevant spatial decision problems. These preference models can also be used to support spatial risk analyses, for instance, in the context of epidemics presented by Zagmutt et al, (4) or incorporating vulnerability to natural disasters, as explored by Zhou et al (5) We will first develop the theory supporting several spatial preference models in Section 2, and then present an example of how one of these models (an additive measurable spatial value function) can be assessed and implemented in Section 3. Section 4 concludes the article.…”
Section: Introductionmentioning
confidence: 99%